Poria cocos beta-glucan composite hydrogel as well as preparation method and application thereof

By using annealing technology to form supramolecular structure in the preparation process of Poria β-glucan composite hydrogel, the problems of unstable network structure and poor mechanical properties of existing polysaccharide hydrogels are solved, and Poria β-glucan composite hydrogels are achieved The mechanical properties of sugar composite hydrogels are improved and drug activity maintenance are suitable for a variety of medical applications.

CN119431901APending Publication Date: 2025-02-14HUBEI ENG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411373197.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the preparation process of existing polysaccharide hydrogels, the network structure is unstable, the mechanical properties are poor, and the drug activity after loading the drug is not ideal.

Method used

Annealing technology is used to mix Poria cocos β-glucan with dimethyl sulfoxide to form a gel polysaccharide/DMSO solution, and assemble it with pure water to form a supramolecular structure to prepare Poria cocos β with more stable network structure and excellent mechanical properties. -Dextran composite hydrogel.

Benefits of technology

The mechanical properties of Poria β-glucan composite hydrogel are improved, and the biological activity of loaded drugs is maximized. It is suitable for antibacterial, anti-inflammatory, antioxidant and skin defect repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431901A_ABST
    Figure CN119431901A_ABST
Patent Text Reader

Abstract

The invention provides poria cocos beta-glucan composite hydrogel. Poria cocos beta-glucan, dimethyl sulfoxide and pure water are used as raw materials; wherein the poria cocos beta-glucan and the dimethyl sulfoxide are mixed to form a gel polysaccharide / DMSO solution, and the gel polysaccharide / DMSO solution and the pure water are assembled into a supramolecular structure through an annealing technology. The invention also provides a preparation method of the tuckahoe beta-glucan composite hydrogel and application of the tuckahoe beta-glucan composite hydrogel in preparation of antibacterial, anti-inflammatory, antioxidant or skin defect repair materials. The tuckahoe beta-glucan composite hydrogel is good in mechanical property, can maintain the biological activity of a loaded drug to the maximum extent, and has application value in the aspects of antibiosis, anti-inflammation, antioxidation and skin defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and in particular to a Poria cocos beta-glucan composite hydrogel and a preparation method and application thereof. Background Art

[0002] The skin is considered an "indispensable barrier" that defends against physical, chemical, and microbial damage, participates in important physiological activities, and plays an important role in maintaining body homeostasis. Therefore, maintaining the integrity of skin tissue is very important for humans. Currently, the therapeutic impedance of skin wounds presents a serious and persistent threat, so it is important to seek new methods for wound repair. Although many biomaterial-based systems have been developed to accelerate wound healing, there is still a great need to develop a new easy-to-manufacture and low-cost system, and curdlan materials show great potential in promoting wound healing.

[0003] Poria cocos β-glucan is a natural polysaccharide polymer that exists in the cell wall of Poria cocos cells. Studies have shown that its structural skeleton can stimulate the human immune system, enhance human resistance, and effectively promote wound repair. Based on this, if Poria cocos β-glucan can be extracted from Poria cocos and combined with other ingredients to form a hydrogel to carry drugs, it can be prepared into a hydrogel drug, which can effectively accelerate wound healing (applied on the wound).

[0004] However, in the preparation of polysaccharide hydrogels in the prior art, polysaccharides and other components mainly exist in the form of "hybrid gels with physical networks", which have unstable network structures, are easily broken, have poor mechanical properties, and have unsatisfactory drug activity after compounding with drugs.

[0005] Therefore, it is urgent to develop a Poria β-glucan composite hydrogel with good mechanical properties and the ability to maintain the biological activity of loaded drugs. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a Poria cocos β-glucan composite hydrogel having good mechanical properties and capable of maintaining the biological activity of loaded drugs, as well as a preparation method and application thereof.

[0007] The present invention adopts the following technical solutions to solve the above technical problems:

[0008] A Poria cocos β-glucan composite hydrogel uses Poria cocos β-glucan, dimethyl sulfoxide (DMSO) and pure water as raw materials; wherein the Poria cocos β-glucan and dimethyl sulfoxide are mixed into a curdlan / DMSO solution, and the curdlan / DMSO solution and pure water are assembled into a supramolecular structure through an annealing technology.

[0009] As one of the preferred embodiments of the present invention, in the curdlan / DMSO solution, the concentration of Poria cocos β-glucan is 1% to 5%, more preferably 4%, and DMSO is used as a solvent.

[0010] As one of the preferred embodiments of the present invention, the mass ratio of the curdlan / DMSO solution to pure water is (1-5):1, more preferably 1:1.

[0011] As one of the preferred embodiments of the present invention, the pure water is sterile water.

[0012] A method for preparing the above-mentioned Poria cocos β-glucan composite hydrogel comprises mixing Poria cocos β-glucan and dimethyl sulfoxide to prepare a curdlan / DMSO solution; heating the curdlan / DMSO solution, adding boiling pure water, and cooling the solution to obtain the desired Poria cocos β-glucan composite hydrogel.

[0013] As one of the preferred embodiments of the present invention, the heating temperature of the curdlan / DMSO solution is 120-200°C, more preferably 200°C.

[0014] As one of the preferred embodiments of the present invention, the cooling rate is 10-30°C / min, more preferably 20°C / min. Too fast a cooling rate will result in a decrease in the strength of the hydrogel.

[0015] As one of the preferred embodiments of the present invention, the temperature after cooling is 10 to 35°C, more preferably 25°C.

[0016] As one of the preferred embodiments of the present invention, after adding pure water and before cooling, a vigorous stirring step is also included, the stirring speed is 500r / s, and the stirring time is 10min. Vigorous stirring can make the polysaccharide and the aqueous solution quickly interweave to form a complex and organized supramolecular structure, and the faster the stirring rate, the more uniform the system and the better the supramolecular network structure; at the same time, in order to avoid excessive stirring rate, resulting in temperature rise and causing liquid boiling, the stirring rate should be controlled not to be too high and the time should not be too long.

[0017] As one of the preferred embodiments of the present invention, the cooling step further includes soaking in water; the soaking temperature is 0-10°C, the soaking time is 48-72h, and more preferably, the soaking temperature is 4°C, and the soaking time is 72h; at the same time, the soaking water is sterile water, and the amount can be adjusted according to the actual situation, so as to at least completely soak the Poria β-glucan composite hydrogel. By soaking in water, the residual organic solvent DMSO can be replaced (DMSO residue will weaken the gel performance and may break during cutting), which is helpful for fixing the gel state.

[0018] An application of the Poria cocos β-glucan composite hydrogel in the preparation of antibacterial, anti-inflammatory, antioxidant or skin defect repairing materials.

[0019] As one of the preferred embodiments of the present invention, the Poria cocos β-glucan composite hydrogel is used as a carrier to carry natural polyphenol drugs as an antibacterial, anti-inflammatory, antioxidant or skin defect repairing material.

[0020] As one of the preferred embodiments of the present invention, the obtained Poria cocos β-glucan composite hydrogel is immersed in a natural polyphenol drug solution and dried to obtain a gel material carrying the natural polyphenol drug.

[0021] As one of the preferred embodiments of the present invention, the natural polyphenol drug is one of gallic acid, tea polyphenols and tannic acid, and more preferably tannic acid.

[0022] Design ideas and principles:

[0023] In the preparation of hydrogels in the prior art, polysaccharides and other components mainly exist in the form of hybrid gels with physical networks, and the network structure is unstable, easy to break, and has poor mechanical properties. In addition, the drug activity after compounding the drug is not ideal. The present invention attempts to assemble the Poria β-glucan / DMSO solution and water into a supramolecular structure through annealing technology, and finds that its structural network is very stable, has better mechanical properties, and after subsequent loading of natural polyphenol drugs, the drug activity can also be maximized.

[0024] Among them, annealing technology is usually a metal heat treatment process, which refers to slowly heating the metal to a certain temperature, keeping it for a sufficient time, and then cooling it at an appropriate speed, with the purpose of reducing hardness and improving machinability; reducing residual stress, stabilizing size, reducing deformation and crack tendency; refining grains, adjusting tissue, and eliminating tissue defects. The present invention introduces annealing technology into the construction of Poria cocos β-glucan composite hydrogel, that is, the system is kept warm at a certain high temperature and then cooled, which can make the hydrogel exist in a supramolecular structure, help stabilize the physical structure of the hydrogel, reduce structural collapse, thereby improving the mechanical properties of the hydrogel, and is conducive to maintaining the activity of the loaded drug.

[0025] The advantages of the present invention compared to the prior art are:

[0026] (1) The present invention adopts annealing technology to construct a Poria cocos β-glucan composite hydrogel with a supramolecular structure, that is, boiling pure water is directly added to a heated curd polysaccharide / DMSO solution in which the polysaccharide is fully dissolved. The obtained Poria cocos β-glucan composite hydrogel has good mechanical properties and can maximize the biological activity of the loaded drug, and has application value in antibacterial, anti-inflammatory, antioxidant, and skin defect repair.

[0027] (2) Compared with other existing gel systems, the Poria cocos β-glucan composite hydrogel material of the present invention has excellent elasticity and mechanical properties and can be cut into various shapes according to needs;

[0028] (3) The preparation method of the present invention is simple and the raw materials are easily available. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a physical picture of the Poria β-glucan composite hydrogel FL-1 to FL-5 and FL-4 / TA in Experimental Example 1;

[0030] Figure 2 It is the degradation test result of Poria β-glucan composite hydrogel FL-1 to FL-5 in Experimental Example 1;

[0031] Figure 3 It is the result of the swelling rate of Poria cocos β-glucan composite hydrogel FL-1 to FL-5 at different times in Experimental Example 1;

[0032] Figure 4 It is the water retention rate result of Poria β-glucan composite hydrogel FL-1 to FL-5 at different time in Experimental Example 1;

[0033] Figure 5 The rheological behavior, elastic modulus and elastic deformation capacity test results of Poria β-glucan composite hydrogels FL-1 to FL-5 in Experimental Example 1 (Figure A is the rheological behavior result; Figure B is the elastic modulus result; Figure C is the elastic deformation capacity result);

[0034] Figure 6 It is the compression performance test result of Poria β-glucan composite hydrogel FL-1 to FL-5 in Experimental Example 1;

[0035] Figure 7 is the release rate of tannic acid in Experimental Example 1 and the scavenging rate of DPPH by the hydrogel at different times (in the figure, Figure A is the release rate result of tannic acid; Figure B is the scavenging rate result of DPPH);

[0036] Figure 8 It is the actual picture and statistical results of the inhibition zone method experiment of the hydrogel on Escherichia coli in Experimental Example 1 (in the figure, Figure A is the actual picture; Figure B is the statistical result);

[0037] Fig. 9 The actual picture and statistical results of the inhibition zone method experiment of the hydrogel on Staphylococcus aureus in Experimental Example 1 (in the figure, Figure A is the actual picture; Figure B is the statistical result);

[0038] Fig.10 It is the result of the ratio of unlysed red blood cells after adding different concentrations of drug-loaded gel to whole blood in Experimental Example 1;

[0039] Fig.11 This is a real picture of the defective skin repair effect of the drug-loaded gel and the simple hydrogel in Experimental Example 1 (with blank treatment and mupirocin ointment treatment as controls);

[0040] Fig.12 This is a statistical chart of the repair effect of defective skin in Experimental Example 1;

[0041] Fig.13 This is the HE staining result of the defective skin repaired in Experimental Example 1 14 days later. DETAILED DESCRIPTION

[0042] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments. At the same time, the reagent products and experimental methods used in the present invention are conventional reagents or methods in the field unless otherwise specified, and will not be repeated.

[0043] Example 1

[0044] The preparation method of the Poria β-glucan composite hydrogel FL-1 in this embodiment is as follows:

[0045] (1) Accurately weigh 100 mg of Poria β-glucan and put it into a 50 mL beaker. Use a pipette to transfer 10 mL of dimethyl sulfoxide into the beaker, place it on a magnetic stirrer and stir at a speed of 500 r / s to dissolve, to prepare a 1% concentration of curdlan / DMSO solution.

[0046] (2) The above-mentioned curdlan / DMSO solution was heated to 200° C. until the Poria β-glucan was completely dissolved; then, 10 mL of boiling pure water was slowly poured into the heated curdlan / DMSO solution at a uniform speed, and stirred at a speed of 500 r / s for 10 min.

[0047] (3) The reacted solution was quickly poured into a corresponding mold and cooled to 25° C. at a cooling rate of 20° C. / min to obtain a Poria β-glucan composite hydrogel.

[0048] (4) The cooled gel was poured into a 500 mL beaker of sterile water and soaked in water at a temperature of 4°C for 72 h, during which the water was changed every 12 h. Finally, the desired Poria β-glucan composite hydrogel with a supramolecular structure was obtained, which was recorded as FL-1.

[0049] Example 2

[0050] A Poria β-glucan composite hydrogel FL-2 in this example is basically the same as Example 1, except that:

[0051] In step (1), 200 mg of Poria β-glucan was accurately weighed and placed in a 50 mL beaker, and 10 mL of dimethyl sulfoxide was pipetted into the beaker, and the mixture was placed on a magnetic stirrer and stirred at 500 r / s to dissolve, thereby preparing a 2% concentration of curdlan / DMSO solution.

[0052] Example 3

[0053] A Poria β-glucan composite hydrogel FL-3 in this example is basically the same as Example 1, except that:

[0054] In step (1): accurately weigh 300 mg of Poria β-glucan and put it into a 50 mL beaker, and use a pipette to transfer 10 mL of dimethyl sulfoxide into the beaker, place it on a magnetic stirrer and stir at a speed of 500 r / s to dissolve, to prepare a 3% concentration of curdlan / DMSO solution.

[0055] Example 4

[0056] A Poria β-glucan composite hydrogel FL-4 in this example is basically the same as Example 1, except that:

[0057] In step (1): accurately weigh 400 mg of Poria β-glucan and put it into a 50 mL beaker, and use a pipette to transfer 10 mL of dimethyl sulfoxide into the beaker, place it on a magnetic stirrer and stir at a speed of 500 r / s to dissolve, to prepare a 4% concentration of curdlan / DMSO solution.

[0058] Example 5

[0059] The Poria β-glucan composite hydrogel FL-5 of this example is basically the same as that of Example 1, except that:

[0060] In step (1), 500 mg of Poria β-glucan was accurately weighed and placed in a 50 mL beaker, and 10 mL of dimethyl sulfoxide was pipetted into the beaker, and the mixture was placed on a magnetic stirrer and stirred at a speed of 500 r / s to dissolve, thereby preparing a 5% concentration of curdlan / DMSO solution.

[0061] Example 6

[0062] The preparation method of the Poria β-glucan composite hydrogel FL-6 in this embodiment is as follows:

[0063] (1) Accurately weigh 400 mg of Poria β-glucan and put it into a 50 mL beaker. Use a pipette to transfer 10 mL of dimethyl sulfoxide into the beaker. Place the mixture on a magnetic stirrer and stir at a speed of 500 r / s to dissolve the mixture, thereby preparing a 4% concentration of curdlan / DMSO solution.

[0064] (2) The above 10 mL of curdlan / DMSO solution was heated to 120° C. until the Poria β-glucan was completely dissolved; then, 5 mL of boiling pure water was slowly poured into the heated curdlan / DMSO solution at a uniform speed, and stirred at a speed of 500 r / s for 10 min.

[0065] (3) The reacted solution was quickly poured into a corresponding mold and cooled to 35° C. at a cooling rate of 10° C. / min to obtain a Poria β-glucan composite hydrogel.

[0066] (4) The cooled gel was poured into a 500 mL beaker of sterile water and soaked in water at a temperature of 0°C for 48 h, during which the water was changed every 12 h. Finally, the desired Poria β-glucan composite hydrogel with a supramolecular structure was obtained, which was recorded as FL-6.

[0067] Example 7

[0068] The preparation method of the Poria β-glucan composite hydrogel FL-7 in this embodiment is as follows:

[0069] (1) Accurately weigh 400 mg of Poria β-glucan and put it into a 50 mL beaker. Use a pipette to transfer 10 mL of dimethyl sulfoxide into the beaker. Place the mixture on a magnetic stirrer and stir at a speed of 500 r / s to dissolve the mixture, thereby preparing a 4% concentration of curdlan / DMSO solution.

[0070] (2) The above 10 mL of curdlan / DMSO solution was heated to 150° C. until the Poria β-glucan was completely dissolved; then, 2 mL of boiling pure water was slowly poured into the heated curdlan / DMSO solution at a uniform speed, and stirred at a speed of 500 r / s for 10 min.

[0071] (3) The reacted solution was quickly poured into a corresponding mold and cooled to 10° C. at a cooling rate of 30° C. / min to obtain a Poria β-glucan composite hydrogel.

[0072] (4) The cooled gel was poured into a 500 mL beaker of sterile water and soaked in water at a temperature of 10°C for 60 h, during which the water was changed every 12 h. Finally, the desired Poria β-glucan composite hydrogel with a supramolecular structure was obtained, which was recorded as FL-7.

[0073] Experimental Example 1

[0074] This experimental example is used to verify the performance of the Poria β-glucan composite hydrogel of the present invention.

[0075] Taking the Poria cocos β-glucan composite hydrogels FL-1 to FL-5 prepared in Examples 1 to 5 as examples, structural characterization and performance testing were performed on them.

[0076] 1. Appearance

[0077] The curdlan / DMSO solution was poured into the mold to obtain a cylindrical composite hydrogel. The hydrogel was initially pale yellow due to the presence of DMSO, but after being soaked in pure water, the DMSO was replaced and the hydrogel became colorless and transparent.

[0078] Figure 1 This is a physical picture of Poria β-glucan composite hydrogel FL-1 to FL-5. In the figure, FL-4 / TA is a control of 4% polysaccharide hydrogel loaded with drug tannic acid.

[0079] Depend on Figure 1 It can be seen that the FL-4 / TA control is yellow in color due to the drug tannic acid, while the hydrogels FL-1 to FL-5 without drugs are all colorless and transparent.

[0080] 2. Degradation performance

[0081] The hydrogel was placed in a phosphate buffer solution at 37°C and its degradation rate was detected at different time points. The results are shown in Figure 2 .

[0082] The results showed that the physicochemical properties of the polysaccharide composite hydrogel supramolecular hydrogels FL-3, FL-4, and FL-5 were relatively stable and not easy to degrade, which is of great significance for long-term wound repair. However, the polysaccharide composite hydrogels FL-1 and FL-2 ruptured after 24 hours of incubation in phosphate buffer solution. This may be due to the fact that the corresponding polysaccharide concentration was too low and the network structure formed was too loose, unlike the hydrogels FL-3, FL-4, and FL-5, which formed a tight structural network at high polysaccharide concentrations and were very stable. Among them, the hydrogel FL-4 showed excellent performance at different time points and had a low degradation rate, which is of great significance for long-term wound repair. It can be cut into various forms according to practical applications and remain stable.

[0083] 3. Water retention and swelling performance

[0084] The hydrogels of different concentrations were immersed in water to obtain their water absorption rate at different times. After reaching stable swelling, they were taken out of the water and their water retention rate after being placed in the air for different times was measured. The results are as follows: Figure 3 Figure 4 shown.

[0085] from Figure 3 , 4The results showed that within 30 hours, the five hydrogels FL-1 to FL-5 swelled rapidly with similar swelling rates; between 30 and 60 hours, FL-1 had a significantly higher swelling rate; after 60 hours, FL-4 and FL-5 had higher swelling rates, with FL-4 having the highest swelling rate; after being placed in the air, the water retention rate of FL-4 decreased more slowly than that of other hydrogels.

[0086] 4. Rheological characteristics

[0087] Rheological behavior, elastic modulus and elastic deformation capacity of hydrogels FL-1 to FL-5 are shown in Figure 2. Figure 5 shown.

[0088] A comprehensive comparison of the storage modulus, loss factor, and loss modulus of hydrogels with different concentrations shows that the storage modulus and loss modulus of FL-4 are better than those of other hydrogels compared with FL-1, 2, 3, and FL-3. This is because FL-4 has a moderate polysaccharide concentration. The internal structure of the hydrogel with a low polysaccharide concentration is unstable and does not form a tighter network structure. The internal structure of the hydrogel with a high polysaccharide concentration is too dense in a limited volume to effectively disperse external forces. Overall, its rheological characteristics are best when the polysaccharide concentration is 4%.

[0089] 5. Stress-strain properties

[0090] The compression test of hydrogels FL-1 to FL-5 revealed the relationship between stress and strain. By studying the strain of the material under different stresses, we can understand the strength, toughness, brittleness and other properties of the material. The results are as follows: Figure 6 shown.

[0091] from Figure 6 The results show that compared with other hydrogels, hydrogel FL-4 has a higher strain capacity under the same stress, which means that it has better toughness, better ductility, and better resistance to external forces.

[0092] 6. Antioxidant Properties

[0093] Taking the hydrogel FL-4 loaded with tannic acid as an example, the DPPH (1,1-diphenyl-2-trinitrophenylhydrazine) method was used to detect the free radical scavenging rate of the hydrogel at different time points to illustrate the antioxidant effect of the hydrogel. Specifically, at 37°C, FL-4 / TA (hydrogel FL-4 loaded with tannic acid) was co-cultured with DPPH in PBS, the liquid was aspirated at different time points, the absorbance value was measured at 517nm, and then compared and calculated to obtain the scavenging rate of tannic acid for different concentrations of DPPH (30min). Among them, the specific operation of loading the hydrogel with tannic acid is: soak the hydrogel in a 10% tannic acid solution for 48h to complete the drug loading.

[0094] The results are as follows Figure 7 As shown. Figure 7 It can be seen from the results that tannic acid is a substance with excellent antioxidant properties; compared with the Poria cocos polysaccharide hydrogel without tannic acid (tested, its scavenging rate for different concentrations of DPPH was 0), the hydrogel soaked in tannic acid showed good antioxidant properties, indicating that Poria cocos hydrogel can be used as a drug carrier to carry tannic acid and exhibit excellent antioxidant properties.

[0095] 7. Antibacterial performance

[0096] Taking the hydrogel FL-4 loaded with tannic acid as an example, the inhibition zone method and co-culture method were used to test the inhibitory effect of the hydrogel on Escherichia coli and Staphylococcus aureus.

[0097] Figure 8 The figure shows the antibacterial effect of the inhibition zone method on Escherichia coli. Fig. 9 The above results show that compared with the blank group (disc filter) without hydrogel and the simple Poria polysaccharide hydrogel (FL), the composite gel (FL / TA) soaked in tannic acid can significantly inhibit the growth of Escherichia coli and Staphylococcus aureus.

[0098] 8. Hemolytic performance

[0099] Taking the hydrogel FL-4 loaded with tannic acid as an example, the corresponding drug-loaded gel FL / TA was freeze-dried and ground into powder, and FL / TA solutions with different concentrations (200 mg / mL, 400 mg / mL) were prepared; the prepared solutions were added to the whole blood, and the hemolysis of red blood cells at different time points was detected, and the solution without FL / TA was used as the control (FL / TA-0). The results are as follows Fig.10 shown.

[0100] Fig.10 The ratio of unlysed red blood cells after adding different concentrations of FL / TA solution to whole blood. The results show that the unlysed rate is greater than 95%, which meets the standards of medical materials.

[0101] 9. Performance in repairing skin defects

[0102] The composite gel FL-4 (FL / TA) soaked in tannic acid and the simple hydrogel (blank gel) were used to repair the defective skin of mice, and the wound recovery was observed at different times. The blank treatment and commercial drug (mupirocin ointment) treatment were used as controls. The results are as follows: Fig.11 , 12 The results showed that the blank gel had no effect on wound repair, while FL / TA could promote skin repair.

[0103] in addition, Fig.13The corresponding HE staining results show that after FL / TA repair, there are fewer inflammatory cells and more collagen fibers, which has a better repair effect.

[0104] In summary, the present invention adopts annealing technology to construct a Poria β-glucan composite hydrogel with a supramolecular structure, that is, boiling pure water is directly added to the curd polysaccharide / DMSO solution in which the polysaccharide is fully dissolved after heating. The obtained Poria β-glucan composite hydrogel has good mechanical properties and can maximize the biological activity of the loaded drug, and has application value in antibacterial, anti-inflammatory, antioxidant, and skin defect repair.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A Poria cocos β-glucan composite hydrogel, characterized in that: The method uses Poria cocos β-glucan, dimethyl sulfoxide and pure water as raw materials; wherein the Poria cocos β-glucan and dimethyl sulfoxide are mixed into a curdlan / DMSO solution, and the curdlan / DMSO solution and pure water are assembled into a supramolecular structure through annealing technology.

2. The Poria cocos β-glucan composite hydrogel according to claim 1, characterized in that: In the curd polysaccharide / DMSO solution, the concentration of Poria cocos β-glucan is 1% to 5%.

3. The Poria cocos β-glucan composite hydrogel according to claim 1, characterized in that: The mass ratio of the curdlan / DMSO solution to pure water is (1-5):

1.

4. A method for preparing the Poria cocos β-glucan composite hydrogel according to any one of claims 1 to 3, characterized in that: Poria cocos beta-glucan and dimethyl sulfoxide are mixed to prepare a curdlan / DMSO solution; the curdlan / DMSO solution is heated, pure water is added, and after cooling, the desired Poria cocos beta-glucan composite hydrogel is obtained.

5. The method for preparing the Poria cocos β-glucan composite hydrogel according to claim 4, characterized in that: The heating temperature of the curdlan / DMSO solution is 120-200°C.

6. The method for preparing the Poria cocos β-glucan composite hydrogel according to claim 4, characterized in that: The cooling rate is 10-30°C / min.

7. The method for preparing the Poria cocos β-glucan composite hydrogel according to claim 4, characterized in that: The temperature after cooling is 10-35°C.

8. The method for preparing the Poria cocos β-glucan composite hydrogel according to claim 4, characterized in that: After cooling, the method further comprises soaking in water; the soaking temperature is 0 to 10° C., and the soaking time is 48 to 72 hours.

9. Use of the Poria cocos β-glucan composite hydrogel according to any one of claims 1 to 3 in the preparation of antibacterial, anti-inflammatory, antioxidant or skin defect repairing materials.

10. The use according to claim 9, characterized in that: The Poria cocos beta-glucan composite hydrogel is used as a carrier to carry natural polyphenol drugs as an antibacterial, anti-inflammatory, antioxidant or skin defect repairing material.

Citation Information

Cited By

  • Bionic synergistically enhanced composite hydrogel and preparation method thereof

    CN121427185A

  • Biomimetic synergistically reinforced composite hydrogel and preparation method thereof

    CN121427185B